The effect of applying the accounting reservation on the quality of the accounting information for the published financial statements – An analytical study of the " Basu" model – - Benzerrouk, Zakia Seid; laamari, Imane Ahmed (Journal of Economic, Administrative and Legal Sciences, 2021)
In his interpretation of the precautionary principle, Basu believes that Conservatism in accounting leads to adverse expectations in most cases, as "bad news" affects profits faster than "good news". He concluded that the precautionary principle implies inconsistent differences between bad news and good news in a timely manner and impedes normally the continuity of the flow of profits. To prove his theory, Basu did a field study based on a study of the sensitivity of the profits of shares of economic companies, to measure the reality of bad news from and good news on the status of profits and the rate of. He found that the return on interest or negative gains are twice to six times greater than the returns of Positive earnings. He emphasized I expect and feel that the sensitivity of profits is greatly influenced by bad news.